SCIENTIFIC ATTITUDE AND ACADEMIC ACHIEVEMENT -A STUDY OF SECONDARY SCHOOL STUDENTS - Mishra, Dr. Sushma (International Journal of Psychosocial Rehabilitation, 2020)
Science has been playing a tremendous role in developing civilization of mankind. Human being is most intelligent creature of nature. Utilizing this intellect only it could reach at this stage of developed world. Only scientific attitude could help human being to reach at this level of development. In the present study an attempt was made to study the academic achievement of secondary school students in relation to their Scientific Attitude. The sample consisted of 520 students (276 girls & 244 boys), selected from 10 different schools of Lucknow city. The main tool used for data collection was Scientific Attitude Scale (SAS) developed by Dr. N.N. Srivastava (for measuring Scientific Attitude). For Academic Achievement, aggregate marks obtained in High School Examination conducted by Uttar Pradesh Board, Prayagraj, was taken as a measure for academic achievement. The result of the study showed that students who were found to possess higher scientific attitude have achieved higher marks in comparison to those whopossess lower scientific attitude. Significant differences were observed at the various components of scientific attitude namely Objectivity, Suspended Judgment, and Rationality, Curiosity, Open Mindedness & Aversion to Superstition and various groups of Academic Achievement, according to norms given in the manual. This is indicative of the fact that students having higher Scientific Attitude perform better academically too. Hence measures should be taken to improve Scientific Attitude of students since childhood through formal and informal education. The study is supposed to be beneficial for policy makers, educational planners, principals, teachers, parents and people from community who are directly or indirectly concerned with the development of children.